Memorandum of Understanding on Internship and Exchange Program between the BRAC University and University of Ottawa (2012) - BDI, BRAC University; FSS & SIDGS, University of Ottawa (BRAC University And University of Ottawa, 2013)
Memorandum of Understanding on Internship and Exchange Program: The AGREEMENT made this June 8, 2012 Between BRAC University, represented by its BRAC Development Institute (BDI), located in Bangladesh and represented by its Faculty of Social Sciences ("FSS") and School of International Development and Global Studies ("SIDGS"), located in OTTAWA, ONTARIO, CANADA